Fc receptors and antibody effector functions - Clark, Mike (Henry Stewart Talks, 2007)
Antibody classes and subclasses, General Ab structure, Modes of action, Fc receptors, General FcR structures, Cellular expression, Triggering by immune complexes, Neonatal FcR, Antibody half-life, Viral FcR, Antibody allotypes, Therapeutic use of monoclonal antibodies, Mechanisms of action, Antiglobulin responses, Antibody humanization